Taking Health Economics and Outcomes Research Forward: Expanding the Definition of Value to Include Whole Health - Pizzi, Laura T.; Abbott, Robert M.; Onukwugha, Eberechukwu (Value in health, 2025)
•ISPOR's Strategic Plan 2030 calls for shaping the definition of value to include whole health.•Examples of whole health applied to HEOR include considering broader outcomes, patient-defined value, and impacts across multiple sectors.•Embracing whole health in HEOR will require interdisciplinary collaboration, enhanced data integration, and inclusive stakeholder engagement to inform evidence development and supporting policies.